Photoresponse high-barrier biodegradable mulching film and preparation method thereof
By using lignin nanoparticles and nanophotocatalysts and combined with plasma treatment, a biodegradable plastic film with asymmetric wetting performance was constructed, which solved the problem of insufficient weather resistance and water vapor barrier properties of traditional plastic films, and achieved efficient water vapor barrier and Pesticide degradation meets environmental protection and sustainable development requirements.
Patent Information
- Application Number
- CN202411507345.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2044-10-28
AI Technical Summary
Traditional low-density polyethylene agricultural mulching is not biodegradable, resulting in soil pollution and microplastic pollution. At the same time, the weather resistance and water vapor barrier properties of existing biodegradable mulching mulching are insufficient, and the use of additives has problems of ecological toxicity and high cost.
Using lignin to prepare nanoparticles as light stabilizers, combined with nanophotocatalysts and plasma treatments, a biodegradable plastic film with asymmetric wetting properties is constructed, which improves its weather resistance and water vapor barrier properties, and realizes directional water transfer and Pesticide degradation.
It has achieved high water vapor barrier, anti-UV aging and directed water transfer properties of biodegradable plastic film, while reducing the harm of pesticides to the environment. It has a simple and efficient process, which is in line with the sustainable development strategy.
Smart Images

Figure CN119161703A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of environmentally friendly materials, and in particular relates to a light-responsive high-barrier biodegradable mulch film and a preparation method thereof. Background Art
[0002] Ground film is an important agricultural production material. It has the functions of warming, moisture conservation, and weed control. It can effectively increase crop yields and quality, and has made significant contributions to ensuring national food security and the supply of agricultural products. However, the recycling rate of traditional low-density polyethylene (LDPE) is low, and nearly 20% of residual film remains in the fields every year. Since LDPE agricultural ground film is not biodegradable, the residual film will destroy the physical and chemical structure of the soil, causing soil compaction, reducing soil porosity and permeability, and reducing crop yields year by year, leading to serious "white pollution" and microplastic pollution.
[0003] Fully biodegradable mulch can be completely degraded by microorganisms into small molecules such as water, carbon dioxide / methane, and minerals under natural conditions, which promotes the formation of new biomass. Polybutylene adipate-terephthalate / polylactic acid (PBAT / PLA) agricultural mulch is the most common fully biodegradable mulch and has been widely used in crops and cash crops. However, the current PBAT / PLA agricultural mulch still has key technical problems such as poor weather resistance and poor water vapor barrier performance. In order to improve the weather resistance of the mulch, the current improved process usually adds chain extenders, light stabilizers, anti-hydrolysis agents and other additives to delay the degradation process of the biodegradable mulch. Patent CN 117866254A discloses "a method for preparing a biodegradable mulch suitable for crops with a long growth cycle". It improves the weather resistance of the mulch by adding ultraviolet absorbers such as benzimidazole. Although it can improve the anti-ultraviolet aging performance of the mulch, these additives have problems such as difficult biodegradation and ecotoxicity, which will cause harm to the ecological environment and human health.
[0004] In addition, the current PBAT biodegradable mulch can solve the plastic pollution problem of LDPE mulch, but there is a problem of poor water vapor barrier performance during use, which limits its promotion and application. Patent CN 118063941A discloses "a high barrier fully biodegradable mulch and its preparation method", which improves the barrier properties of the mulch by adding water vapor barrier and nano-montmorillonite. However, the water vapor barrier and nano-particles such as montmorillonite are easy to agglomerate and have poor dispersion when melt blended. Patent CN118344714A discloses "a functional masterbatch that can improve the water barrier properties of biological boundary surface mulch and its application". The invention uses hydrophobic additives such as beeswax and palm wax to improve the barrier properties of the mulch. Although it can reduce the water vapor permeability of the mulch, it affects the gas permeability of the mulch, inhibits the normal respiration of soil microorganisms, and also increases the production cost of the mulch. Summary of the invention
[0005] In view of the above-mentioned problems existing in the prior art, the present invention provides a light-responsive high-barrier biodegradable mulch film and a preparation method thereof, which utilizes lignin to prepare lignin nanoparticles, and uses the lignin nanoparticles as a light stabilizer to improve the weather resistance of the biodegradable mulch film; and by doping with nano-photocatalysts, the surface of the mulch film is made super-hydrophilic under light; at the same time, plasma treatment is used to perform hydrophobic modification on one side of the mulch film to improve the barrier properties of the mulch film, thereby constructing a biodegradable mulch film with asymmetric wetting properties, which can realize directional water transport of droplets under light-responsive conditions; at the same time, the nano-photocatalysts on the surface can degrade residual pesticides and reduce the harm of pesticides to the environment.
[0006] To achieve the above object, the present invention adopts the following technical solution: A photoresponsive high-barrier biodegradable mulch film with asymmetric wettability, i.e., one side is super-hydrophobic (water contact angle is 150°~165°) and the other side is hydrophilic, thus having excellent water vapor barrier performance and directional water transport performance, and its water vapor permeability is less than 400g / m 2 ·d, fog water collection efficiency is greater than 50g / h·m 2 , elongation at break (longitudinal and transverse) greater than 250%, tensile strength (longitudinal and transverse) greater than 1.5N, and elongation at break (longitudinal and transverse) greater than 100% after aging under ultraviolet radiation for 100h. After 48 hours of simulated sunlight, the removal rate of 0.1% imidacloprid insecticide is greater than 96.2%.
[0007] The method for preparing the light-responsive high-barrier biodegradable mulch film comprises the following steps: 1) Preparation of lignin nanoparticles: dissolving pulping black liquor in deionized water, filtering to remove impurities, adjusting the pH value of the filtrate to 2-3, washing the precipitate with water, filtering, and drying to obtain purified lignin powder; dissolving the purified lignin powder in acetic anhydride, heating and stirring at 60-90° C. for 2-4 hours, and then evaporating under reduced pressure to obtain acetylated lignin; then re-dissolving the acetylated lignin in deionized water, and adding dropwise to a 5% hydrochloric acid solution, washing the obtained precipitate with water, and drying to obtain lignin nanoparticles; 2) Preparation of biodegradable mulch film: biodegradable resin, lignin nanoparticles, shell powder, chain extender, anti-hydrolysis agent, and nano-photocatalyst are mixed in proportion, and then granulated by a twin-screw extruder, and then cast by a casting machine to obtain a biodegradable mulch film; 3) Plasma hydrophobic modified mulch: The biodegradable mulch prepared in step 2) is placed in a low-temperature plasma treatment device, and a modified gas is introduced to perform plasma hydrophobic modification on one side of the biodegradable mulch, thereby obtaining a light-responsive high water vapor barrier biodegradable mulch with asymmetric wettability.
[0008] Furthermore, in step 1), the pulping black liquor is collected after pulping one or more of rice straw, wheat straw, reed, bagasse, bamboo, masson pine, poplar, eucalyptus, and birch by caustic soda method, sulfate method, or sulfite method; wherein the lignin content is 10-50%, and the density is 1.02-1.58 g / mL.
[0009] Furthermore, the mass ratio of the purified lignin powder to acetic anhydride used in step 1) is 1:2-3.
[0010] Furthermore, in step 2), the biodegradable resin is one or more of polybutylene adipate / terephthalate (PBAT), polylactic acid (PLA), polypropylene carbonate (PPC), polyhydroxyalkanoate (PHA), and polybutylene succinate (PBS).
[0011] Furthermore, the shell powder in step 2) is obtained by washing, crushing and grinding the shells of one or more of oysters, scallops, clams and conches, and has a fineness of 1500-2000 mesh.
[0012] Furthermore, in step 2), the chain extender is one or more of styrene-glycidyl methacrylate, diphenylmethane diisocyanate, acetyl tributyl citrate, ADR-4368, ADR-4370, ADR-4400, and ADR-4468.
[0013] Furthermore, the anti-hydrolysis agent in step 2) is one or more of carbodiimide, isocyanate, and epoxy compound.
[0014] Furthermore, the nano photocatalyst in step 2) is one of titanium dioxide, zinc oxide, manganese dioxide and copper oxide.
[0015] Furthermore, in parts by weight, the amounts of the materials used in step 2) are: 60-90 parts of biodegradable resin, 1-3 parts of lignin nanoparticles, 5-10 parts of shell powder, 0.2-1 parts of chain extender, 0.2-1 parts of anti-hydrolysis agent, and 0.05-0.2 parts of nano-photocatalyst.
[0016] Furthermore, in step 2), the temperature range of each zone of the twin-screw extruder is 140-160° C., the die temperature is 145-155° C., and the screw speed is 400-600 rpm / min.
[0017] Furthermore, in step 2), the temperature of each zone of the casting machine is 150-165°C, the die temperature is 165°C, the distance between the extruder die and the casting roller is 250 mm, the temperature of the casting roller is 60-70°C, and the casting draw ratio is 60-100.
[0018] Furthermore, in step 3), the modified gas is one or more of CF4, CHF3, C2F6, and SF6.
[0019] Furthermore, in step 3), the vacuum degree of the plasma hydrophobic modification is 10 -2 ~10 -3 mbar, power is 60~130W, and processing time is 5~15min.
[0020] Lignin is the second most abundant biomass on earth. Its molecular structure contains functional groups such as aromatic, phenolic hydroxyl, ketone and carboxyl groups, as well as intramolecular hydrogen bonds and conjugated structures, which give lignin anti-ultraviolet radiation and antioxidant properties. Although lignin has a certain ability to absorb ultraviolet light, its structure contains a large number of hydrophilic groups such as hydroxyl groups, which have poor compatibility with biodegradable resins such as polybutylene adipate / terephthalate (PBAT), affecting its application in the field of biodegradable plastics. The present invention prepares lignin nanoparticles by acetylation of lignin, improves the hydrophobic properties of lignin, improves its interfacial compatibility, solves the problem of poor compatibility between lignin and biodegradable plastics, and uses it to replace small molecule light stabilizers in biodegradable mulch films, which can improve the anti-ultraviolet aging performance of the mulch films, and effectively solves the problem of easy migration and difficult biodegradation of small molecule light stabilizers.
[0021] The present invention uses plasma hydrophobic modification to make the side of the mulch film contacting the soil have super hydrophobic properties, thereby improving the water vapor barrier performance of the mulch film; and through the addition of nano photocatalysts, the side of the mulch film facing the sunlight has hydrophilic properties, thereby constructing an asymmetric wetting property biodegradable mulch film with one side hydrophilic and the other side hydrophobic, which has excellent water vapor barrier properties and can achieve directional water transport of droplets under light response conditions. In addition, the mulch film doped with photocatalytic nanoparticles can degrade pesticides adsorbed on the surface under light, reducing the harm of pesticides to the environment.
[0022] Compared with the prior art, the present invention has the following advantages and positive effects: (1) The present invention uses pulping black liquor as raw material to prepare lignin nanoparticles, which is not only low-cost, but also makes use of waste resources and high-value utilization of by-products of pulping and papermaking, which is in line with the national circular economy and sustainable development strategy. At the same time, replacing small molecule light stabilizers with lignin nanoparticle light stabilizers can solve the current problems of easy migration and environmental toxicity of small molecule light stabilizers.
[0023] (2) The present invention uses plasma technology to replace the modified mulch containing hydrophobic finishing agents, making the mulch have super hydrophobic properties. It does not change the structure of the membrane, nor does it affect the air permeability of the mulch, solving the environmental pollution problem of existing fluorine-containing finishing agents; at the same time, by doping photocatalytic nanoparticles, the illuminated side of the mulch also has hydrophilic properties and photocatalytic degradation of pesticides. Since the constructed mulch has asymmetric wetting properties, it has high water vapor barrier and light-responsive droplet directional water transport properties.
[0024] (3) The preparation process of the present invention is simple, efficient, green and environmentally friendly. The prepared light-responsive high-barrier biodegradable mulch film has excellent water vapor barrier properties and anti-ultraviolet aging properties, and also has the ability of directional water transport and photocatalytic degradation of pesticides, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 It is a schematic diagram of using the light-responsive high-barrier biodegradable mulch film of the present invention.
[0026] Figure 2 This is the infrared spectrum of the biodegradable mulch prepared in Examples 1-4.
[0027] Figure 3 The contact angles of the biodegradable mulches prepared in Examples 1-4.
[0028] Figure 4 The scanning electron microscope images of the brittle fracture surfaces of the biodegradable mulch films prepared in Examples 1-4 and Comparative Example 2 are shown. DETAILED DESCRIPTION
[0029] A photoresponsive high-barrier biodegradable mulch film, the preparation of which comprises the following steps: 1) Preparation of lignin nanoparticles: dissolving pulping black liquor in deionized water, filtering to remove impurities, then dropping hydrochloric acid to adjust the pH value of the filtrate to 2-3, washing the precipitate with deionized water, filtering, and drying to obtain purified lignin powder (AL); dissolving the purified lignin powder in acetic anhydride at a mass ratio of 1:2-3, heating and stirring at 60-90°C for 2-4h, and then evaporating under reduced pressure at 60°C and -0.1mpa in a rotary evaporator to obtain acetylated lignin (ACAL); then redissolving the acetylated lignin in deionized water, and dropping it into a 5% hydrochloric acid solution, washing the obtained precipitate with water, and drying to obtain lignin nanoparticles; 2) Preparation of biodegradable mulch film: by weight, add 60-90 parts of biodegradable resin, 1-3 parts of lignin nanoparticles, 5-10 parts of shell powder, 0.2-1 parts of chain extender, 0.2-1 parts of anti-hydrolysis agent, and 0.05-0.2 parts of nano photocatalyst into a mixer, mix for 5-10 minutes, then granulate with a twin-screw extruder, and then cast with a casting machine to obtain a biodegradable mulch film; 3) Plasma hydrophobic modified mulch: Place the biodegradable mulch prepared in step 2) into a low-temperature plasma treatment device and set the vacuum degree to 10 -2 ~10 -3 mbar, introduce modified gas, set the plasma treatment power to 60-130 W, and the treatment time to 5-15 min, to perform hydrophobic modification on one side of the biodegradable mulch film, thereby obtaining a light-responsive high water vapor barrier biodegradable mulch film.
[0030] In step 1), the pulping black liquor is collected after pulping one or more of rice straw, wheat straw, reed, bagasse, bamboo, masson pine, poplar, eucalyptus, and birch by caustic soda method, sulfate method, or sulfite method; wherein the lignin content is 10-50%, and the density is 1.02-1.58 g / mL.
[0031] Step 2) The biodegradable resin is one or more of polybutylene adipate / terephthalate (PBAT), polylactic acid (PLA), polypropylene carbonate (PPC), polyhydroxyalkanoate (PHA), and polybutylene succinate (PBS); the shell powder is obtained by washing, crushing, and grinding the shells of one or more of oysters, scallops, clams, and conches, and its fineness is 1500-2000 mesh; the chain extender is one or more of styrene-methylglycidyl methacrylate, diphenylmethane diisocyanate, acetyl tributyl citrate, ADR-4368, ADR-4370, ADR-4400, and ADR-4468; the anti-hydrolysis agent is one or more of carbodiimide, isocyanate, and epoxy compound; the nano photocatalyst is one of titanium dioxide, zinc oxide, manganese dioxide, and copper oxide.
[0032] Step 2) The temperature range of each zone of the twin-screw extruder is 140-160°C, the die temperature is 145-155°C, and the screw speed is 400-600 rpm / min. The temperature of each zone of the casting machine is 150-165°C, the die temperature is 165°C, the distance between the extruder die and the casting roller is 250mm, the temperature of the casting roller is 60-70°C, and the casting draft ratio is 60-100.
[0033] Step 3) The modified gas is one or more of CF4, CHF3, C2F6, and SF6.
[0034] The present invention is described in detail below through examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art can make some non-essential improvements and adjustments based on the contents of the present invention, which still fall within the scope of protection of the present invention.
[0035] The raw materials used in the examples are described below: The pulping black liquor comes from an enterprise in Nanping, Fujian, and the other raw materials come from common commercially available medicines and additives in this field.
[0036] Example 1 (1) Preparation of lignin nanoparticles: 5 kg of 25% solid content kraft pulped Masson pine black liquor was dissolved in 5 L of deionized water, stirred evenly and filtered to remove impurities, then 20% hydrochloric acid solution was added to the filtrate to adjust the pH to 2, the acid precipitated lignin was washed 3 times with deionized water, filtered and dried in vacuum at 60 °C to obtain purified lignin powder. 1 kg of purified lignin was dissolved in 2.5 kg of acetic anhydride, heated and stirred at 70 °C for 2 h, and then evaporated under reduced pressure at 60 °C and -0.1 MPa in a rotary evaporator to obtain acetylated lignin. The acetylated lignin was redissolved in deionized water and added dropwise to 5% hydrochloric acid solution. The precipitate was washed 3 times with deionized water and dried in a vacuum oven at 60 °C to obtain lignin nanoparticles.
[0037] (2) Preparation of biodegradable mulch film: Weigh 65 kg PBAT, 10 kg PPC and 5 kg PLA, 1 kg lignin nanoparticles, 5 kg shell powder (2000 mesh, processed from oyster shells), 0.2 kg diphenylmethane diisocyanate, 0.2 kg carbodiimide, and 0.08 kg nano-titanium dioxide, add them into a mixer in sequence and mix for 10 min, then use a twin-screw extruder to granulate, and then add them into a casting machine to obtain a PBAT / PPC / PLA biodegradable mulch film.
[0038] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 140°C, 140°C, 145°C, 145°C, 145°C, 150°C, and 150°C, the die temperature is 150°C, and the screw speed is 400 rpm / min.
[0039] The working parameters of the casting machine are: the temperatures of the first 5 zones of the casting film machine are 150℃, 150℃, 155℃, 160℃, and 165℃, the die temperature is 165℃, the distance between the extruder die and the casting roller is 250mm, the casting roller temperature is 70℃, and the casting draw ratio is 80.
[0040] (3) Plasma hydrophobic modified mulch: Place the biodegradable mulch prepared in step (2) into a low-temperature plasma treatment device and evacuate to a vacuum degree of 10 -3 mbar, introduced CF4 gas, turned on the plasma source, set the time to 10 min, and the plasma processing power to 80 w to obtain a light-responsive high-barrier biodegradable mulch film with a thickness of 10 μm.
[0041] Example 2 (1) Preparation of lignin nanoparticles: 5 kg of eucalyptus black liquor obtained by sulfite pulping with a solid content of 30% was dissolved in 5 L of deionized water, stirred evenly and filtered to remove impurities, and then a 20% hydrochloric acid solution was added to the filtrate to adjust the pH value to 2. The acid precipitated lignin was washed with deionized water three times, filtered and dried in a vacuum oven at 60°C to obtain purified lignin powder. 1 kg of purified lignin was dissolved in 2.5 kg of acetic anhydride, stirred at 75°C for 2 h, and then evaporated under reduced pressure at 60°C and -0.1 MPa in a rotary evaporator to obtain acetylated lignin. The acetylated lignin was redissolved in deionized water and added dropwise to a 5% hydrochloric acid solution. The precipitate was washed with deionized water three times and dried in a vacuum oven at 60°C to obtain lignin nanoparticles.
[0042] (2) Preparation of biodegradable mulch film: Weigh 60 kg PBAT, 10 kg PPC, 3 kg PBS and 5 kg PLA, 1.2 kg lignin nanoparticles, 8 kg shell powder (2000 mesh, obtained from oyster shells), 0.2 kg ADR-4368, 0.2 kg isophorone diisocyanate, and 0.1 kg nano zinc oxide, add them into a mixer in sequence and mix for 10 min, then granulate them using a twin-screw extruder, and then use a casting machine to make a PBAT / PPC / PBS / PLA biodegradable mulch film.
[0043] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 140°C, 145°C, 145°C, 150°C, 150°C, 155°C, and 155°C, the die temperature is 155°C, and the screw speed is 400 rpm / min.
[0044] The working parameters of the casting machine are: the temperatures of the first 5 zones of the casting film machine are 150℃, 155℃, 155℃, 160℃, and 165℃, the die temperature is 165℃, the distance between the extruder die and the casting roller is 250mm, the casting roller temperature is 75℃, and the casting stretch ratio is 65.
[0045] (3) Plasma hydrophobic modified mulch: The biodegradable mulch prepared in step (2) is placed in a low-temperature plasma treatment device and evacuated to a vacuum degree of 10 -3 mbar, introduced C2F6 gas, turned on the plasma source, set the time to 10 min, and the plasma processing power to 70 w to obtain a light-responsive high-barrier biodegradable mulch film with a thickness of 10 μm.
[0046] Example 3 (1) Preparation of lignin nanoparticles: 5 kg of poplar black liquor obtained by kraft pulping with a solid content of 28% was dissolved in 5 L of deionized water, stirred evenly and filtered to remove impurities, then a 20% hydrochloric acid solution was added to the filtrate to adjust the pH value to 2, and the acid precipitated lignin was washed with deionized water three times, filtered and dried in a vacuum oven at 60°C to obtain purified lignin powder. 1 kg of purified lignin was dissolved in 3 kg of acetic anhydride, stirred at 75°C for 2.5 h, and then evaporated under reduced pressure at 60°C and -0.1 MPa in a rotary evaporator to obtain acetylated lignin. The acetylated lignin was redissolved in deionized water and added dropwise to a 5% hydrochloric acid solution. The resulting precipitate was washed with deionized water three times and dried in a vacuum oven at 60°C to obtain lignin nanoparticles.
[0047] (2) Preparation of biodegradable mulch film: Weigh 55 kg PBAT, 15 kg PPC, 5 kg PHA and 5 kg PLA, 1.5 kg lignin nanoparticles, 8 kg shell powder (2000 mesh, obtained from oyster shells), 0.3 kg ADR-4468, 0.4 kg carbodiimide, and 0.1 kg nano copper oxide, add them into a mixer in sequence and mix for 10 min, then granulate them using a twin-screw extruder, and then use a casting machine to make PBAT / PPC / PHA / PLA biodegradable mulch film.
[0048] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 140°C, 145°C, 145°C, 150°C, 150°C, 160°C, and 155°C, the die temperature is 155°C, and the screw speed is 400 rpm / min.
[0049] The working parameters of the casting machine are: the temperatures of the first 5 zones of the casting film machine are 150℃, 150℃, 155℃, 160℃, and 165℃, the die temperature is 165℃, the distance between the extruder die and the casting roller is 250mm, the casting roller temperature is 75℃, and the casting stretch ratio is 65.
[0050] (3) Plasma hydrophobic modified mulch: Place the biodegradable mulch prepared in step (2) into a low-temperature plasma treatment device and evacuate to a vacuum degree of 10 -3 mbar, introduced CF4 gas, turned on the plasma source, set the time to 10 min, and the plasma processing power to 75 w to obtain a light-responsive high-barrier biodegradable mulch film with a thickness of 10 μm.
[0051] Example 4 (1) Preparation of lignin nanoparticles: 5 kg of bamboo black liquor obtained by sulfate pulping with a solid content of 33% was dissolved in 5 L of deionized water, stirred evenly and filtered to remove impurities, and then a 20% hydrochloric acid solution was added to the filtrate to adjust the pH value to 2. The acid precipitated lignin was washed with deionized water three times, filtered and dried in a vacuum oven at 60°C to obtain purified lignin powder. 1 kg of purified lignin was dissolved in 3.0 kg of acetic anhydride, stirred at 70°C for 2 h, and then evaporated under reduced pressure at 60°C and -0.1 MPa in a rotary evaporator to obtain acetylated lignin. The acetylated lignin was redissolved in deionized water and added dropwise to a 5% hydrochloric acid solution. The precipitate was washed with deionized water three times and dried in a vacuum oven at 60°C to obtain lignin nanoparticles.
[0052] (2) Preparation of biodegradable mulch film: 55 kg PBAT, 10 kg PPC and 10 kg PBS, 2 kg lignin nanoparticles, 8 kg shell powder (2000 mesh, obtained from oyster shells), 0.3 kg ADR-4400, 0.3 kg carbodiimide, and 0.1 kg nano-titanium dioxide were weighed and added into a mixer in sequence and mixed for 10 min. The mixture was then granulated using a twin-screw extruder and subsequently made into a PBAT / PPC / PBS biodegradable mulch film using a casting machine.
[0053] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 145°C, 145°C, 150°C, 155°C, 160°C, 155°C, and 155°C, the die temperature is 155°C, and the screw speed is 400 rpm / min.
[0054] The working parameters of the casting machine are: the temperatures of the first 5 zones of the cast film machine are 155℃, 160℃, 160℃, 165℃, and 165℃, the die temperature is 165℃, the distance between the extruder die and the casting roller is 250mm, the casting roller temperature is 75℃, and the casting stretch ratio is 75.
[0055] (3) Plasma hydrophobic modified mulch: Place the biodegradable mulch prepared in step (2) into a low-temperature plasma treatment device and evacuate to a vacuum degree of 10 -3 mbar, introduced CF4 gas, turned on the plasma source, set the time to 15 min, and the plasma processing power to 80 w to obtain a light-responsive high-barrier biodegradable mulch film with a thickness of 10 μm.
[0056] Comparative Example 1 (1) Preparation of lignin nanoparticles: 5 kg of 25% solid content kraft pulped Masson pine black liquor was dissolved in 5 L of deionized water, stirred evenly and filtered to remove impurities, then 20% hydrochloric acid solution was added to the filtrate to adjust the pH to 2, the acid precipitated lignin was washed 3 times with deionized water, filtered and dried in vacuum at 60 °C to obtain purified lignin powder. 1 kg of purified lignin was dissolved in 2.5 kg of acetic anhydride, heated and stirred at 70 °C for 2 h, and then evaporated under reduced pressure at 60 °C and -0.1 MPa in a rotary evaporator to obtain acetylated lignin. The acetylated lignin was redissolved in deionized water and added dropwise to 5% hydrochloric acid solution. The precipitate was washed 3 times with deionized water and dried in a vacuum oven at 60 °C to obtain lignin nanoparticles.
[0057] (2) Preparation of biodegradable mulch film: 65 kg PBAT, 10 kg PPC and 5 kg PLA, 1 kg lignin nanoparticles, 5 kg shell powder (2000 mesh, processed from oyster shells), 0.2 kg diphenylmethane diisocyanate, 0.2 kg carbodiimide, and 0.08 kg nano-titanium dioxide were weighed and added into a mixer in sequence and mixed for 10 min. Then, granulation was performed using a twin-screw extruder, and then a casting machine was used to form a PBAT / PPC / PLA biodegradable mulch film with a thickness of 10 μm.
[0058] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 140°C, 140°C, 145°C, 145°C, 145°C, 150°C, and 150°C, the die temperature is 150°C, and the screw speed is 400 rpm / min.
[0059] The working parameters of the casting machine are: the temperatures of the first 5 zones of the casting film machine are 150℃, 150℃, 155℃, 160℃, and 165℃, the die temperature is 165℃, the distance between the extruder die and the casting roller is 250mm, the casting roller temperature is 70℃, and the casting draw ratio is 80.
[0060] Comparative Example 2 (1) Preparation of lignin powder: 5 kg of bamboo black liquor obtained by sulfate pulping with a solid content of 33% was dissolved in 5 L of deionized water, stirred evenly and filtered to remove impurities, and then 20% hydrochloric acid solution was added dropwise to the filtrate to adjust the pH value to 2. The obtained acid-precipitated lignin was washed three times with deionized water, filtered and dried in vacuum at 60°C to obtain purified lignin powder.
[0061] (2) Preparation of biodegradable mulch film: Weigh 55 kg PBAT, 10 kg PPC and 10 kg PBS, 2 kg purified lignin powder, 8 kg shell powder (2000 mesh, obtained from oyster shells), 0.3 kg ADR-4400, 0.3 kg carbodiimide, and 0.1 kg nano-titanium dioxide, add them into a mixer in sequence and mix for 10 min, then granulate them using a twin-screw extruder, and then use a casting machine to make PBAT / PPC / PBS biodegradable mulch film.
[0062] The working parameters for granulation are as follows: the temperatures of the first 7 zones of the twin-screw extruder are 145°C, 145°C, 150°C, 155°C, 160°C, 155°C, and 155°C, the die temperature is 155°C, and the screw speed is 400 rpm / min.
[0063] The working parameters of the casting machine are: the temperatures of the first 5 zones of the cast film machine are 155℃, 160℃, 160℃, 165℃, and 165℃, the die temperature is 165℃, the distance between the extruder die and the casting roller is 250mm, the casting roller temperature is 75℃, and the casting stretch ratio is 75.
[0064] (3) Plasma hydrophobic modified mulch: Place the biodegradable mulch prepared in step (2) into a low-temperature plasma treatment device and evacuate to a vacuum degree of 10 -3 mbar, introduced CF4 gas, turned on the plasma source, set the time to 15 min, and the plasma treatment power to 80 w to obtain a biodegradable mulch with a thickness of 10 μm.
[0065] 1. Infrared spectroscopy (FTIR) analysis Figure 2 This is the infrared spectrum of the biodegradable mulch prepared in Example 1-4. As shown in the figure, 1650cm -1 is the stretching vibration peak of the carbonyl group (C=O) in the biodegradable resin; in addition, due to the addition of lignin nanoparticles, the biodegradable mulch films in the examples all showed a peak of 1597 cm -1 Characteristic absorption peak of lignin benzene ring.
[0066] 2. Contact angle of biodegradable mulch Figure 3 The water contact angle comparison diagram of the biodegradable mulch prepared in Examples 1 to 4. As shown in the figure, both sides of the biodegradable mulch prepared in Examples 1 to 4 exhibit asymmetric wettability, forming a gradient wettability, which can realize the directional water conduction function of the mulch.
[0067] 3. Scanning electron microscope (SEM) image of brittle section Figure 4The scanning electron microscope images of the brittle fracture surfaces of the biodegradable mulch films prepared in Examples 1-4 and Comparative Example 2 show that the prepared lignin nanoparticles are spherical and have a relatively uniform size. They are evenly dispersed in the biodegradable mulch films, indicating that they have good compatibility with the biodegradable resin.
[0068] 4. Performance Testing The performance tests were conducted on the biodegradable mulch films prepared in the examples and comparative examples. The results are shown in Tables 1 and 2.
[0069] a. Moisture permeability: Tested using GB / T 1037-2021 cup method (proliferation method).
[0070] b. Fog water collection efficiency: In a constant temperature and humidity chamber, the relative humidity was maintained at 90%, 30 g of anhydrous calcium carbonate particles were placed in the moisture permeable cup, and the moisture permeable cup was covered with mulch. A 24-hour fog collection experiment was conducted, and the weight of the moisture permeable cup was weighed every 1 hour.
[0071] c. Imidacloprid insecticide removal rate: A 0.1% imidacloprid solution was sprayed on the surface of the mulch film, and then exposed to simulated sunlight for 48 hours and then immersed in deionized water. The imidacloprid concentration in the water was tested by high performance liquid chromatography. At the same time, the mulch film that had not been exposed to light was tested and the imidacloprid removal rate was calculated.
[0072] d. UV aging performance: According to GB / T 16422.2-2014, the aging cycle conditions include 102 min of light exposure (0.51 W / (m 2 ·nm) and then spray for 18min, blackboard temperature 65±3℃, aging test 100h. The mechanical properties of the samples before and after UV aging were tested to verify the film's anti-UV aging performance. The mechanical properties test was carried out on a universal mechanical testing machine in accordance with GB / T1040-2003 standard to test the tensile properties of the ground film, with a tensile speed of 250mm / min, and 5 parallel samples were tested for each group of samples.
[0073] Table 1 Test results of physical and chemical properties of biodegradable mulch films prepared in Examples and Comparative Examples
[0074] Table 2 UV aging performance test results of biodegradable mulch films prepared in Examples and Comparative Examples
[0075] From the results shown in Table 1, it can be seen that after one side of the biodegradable mulch prepared in the example is modified by plasma, its water contact angle is significantly increased, and it has super hydrophobic properties, which significantly improves its water vapor barrier performance. At the same time, by constructing asymmetric wetting properties, directional water transport of droplets under light response conditions can be achieved, thereby improving the mulch's ability to collect fog water.
[0076] From the results shown in Table 2, it can be seen that the different types of biodegradable mulches prepared in the examples still have good mechanical properties after UV aging for 100 hours, and the elongation at break is greater than 150%, indicating that the biodegradable mulches prepared in the present invention have excellent anti-UV aging performance.
[0077] The above description is only a preferred embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.
Claims
1. A light-responsive high-barrier biodegradable mulch film, characterized in that: The biodegradable mulch film has asymmetric wetting properties, that is, one side is super hydrophobic and the other side is hydrophilic, so that it has excellent water vapor barrier properties and directional water transport properties.
2. A method for preparing the light-responsive high-barrier biodegradable mulch film as claimed in claim 1, characterized in that: The following steps are involved: 1) Preparation of lignin nanoparticles: dissolving pulping black liquor in deionized water, filtering to remove impurities, adjusting the pH value of the filtrate to 2-3, washing the precipitate with water, filtering, and drying to obtain purified lignin powder; dissolving the purified lignin powder in acetic anhydride, heating and stirring at 60-90°C for 2-4h, and then evaporating under reduced pressure to obtain acetylated lignin; then re-dissolving the acetylated lignin in deionized water, and adding dropwise to a 5% hydrochloric acid solution, washing the obtained precipitate with water, and drying to obtain lignin nanoparticles; 2) Preparation of biodegradable mulch film: biodegradable resin, lignin nanoparticles, shell powder, chain extender, anti-hydrolysis agent, and nano-photocatalyst are mixed in proportion, and then granulated by a twin-screw extruder, and then cast by a casting machine to obtain a biodegradable mulch film; 3) Plasma hydrophobic modified mulch: The biodegradable mulch prepared in step 2) is placed in a low-temperature plasma treatment device, and a modified gas is introduced to perform plasma hydrophobic modification on one side of the biodegradable mulch, thereby obtaining a light-responsive high water vapor barrier biodegradable mulch with asymmetric wettability.
3. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: Step 1) The pulping black liquor is collected after pulping one or more of rice straw, wheat straw, reed, bagasse, bamboo, masson pine, poplar, eucalyptus, and birch by caustic soda method, sulfate method, or sulfite method; wherein the lignin content is 10-50%, and the density is 1.02-1.58 g / mL.
4. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: The mass ratio of the purified lignin powder to acetic anhydride used in step 1) is 1:2-3.
5. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: In parts by weight, the amount of each material used in step 2) is: 60-90 parts of biodegradable resin, 1-3 parts of lignin nanoparticles, 5-10 parts of shell powder, 0.2-1 parts of chain extender, 0.2-1 parts of anti-hydrolysis agent, and 0.05-0.2 parts of nano photocatalyst.
6. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2 or 5, characterized in that: The biodegradable resin is one or more of polybutylene adipate / terephthalate, polylactic acid, polypropylene carbonate, polyhydroxyalkanoate, and polybutylene succinate; The shell powder is obtained by washing, crushing and grinding the shells of one or more of oysters, scallops, clams and conches, and the fineness thereof is 1500-2000 meshes; The chain extender is one or more of styrene-glycidyl methacrylate, diphenylmethane diisocyanate, acetyl tributyl citrate, ADR-4368, ADR-4370, ADR-4400, and ADR-4468; The anti-hydrolysis agent is one or more of carbodiimide, isocyanate and epoxy compound; The nano photocatalyst is one of titanium dioxide, zinc oxide, manganese dioxide and copper oxide.
7. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: Step 2) The temperature range of each zone of the twin-screw extruder is 140-160°C, the die temperature is 145-155°C, and the screw speed is 400-600 rpm / min.
8. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: Step 2) The temperature of each zone of the casting machine is 150-165°C, the die temperature is 165°C, the distance between the extruder die and the casting roller is 250 mm, the temperature of the casting roller is 60-70°C, and the casting draft ratio is 60-100.
9. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: Step 3) The modified gas is one or more of CF4, CHF3, C2F6, and SF6.
10. The method for preparing the light-responsive high-barrier biodegradable mulch film according to claim 2, characterized in that: Step 3) The vacuum degree of the plasma hydrophobic modification is 10 -2 ~10 -3 mbar, power is 60~130W, and processing time is 5~15min.
Citation Information
Patent Citations
High-barrier full-biodegradable mulching film and preparation method thereof
CN118063941A
Functional master batch capable of improving water resistance of biological state mulching film and application of functional master batch
CN118344714A
Water-collecting degradable mulching film and preparation method thereof
CN110628187A
Light-driven single-layer Janus oil-water separation membrane and preparation method thereof
CN115646221A
Super-hydrophobic paper mulching film as well as preparation method and application thereof
CN115726216A
Cited By
High-barrier and anti-aging mulching film and preparation method thereof
CN121406093A
